Ecosystem services of the city campus: carbon landfill of the RUDN-University - M.M, Redina; E.V., Savenkova (Universitas Diponegoro, 2022)
The approaches to the organization and the first results of the project on the organization of a carbon landfill at the Peoples ' Friendship University of Russia are presented. The topic of the absorption of greenhouse gases by natural ecosystems is one of the most actively developing. A complex of scientific and educational projects on climate change, decarbonization, and assessment of ecosystem services is being implemented at the RUDN University. One of the directions is our own carbon landfill on the campus. The object is of interest as a technologically modified ecosystem that is under the influence of anthropogenic sources. The analysis of ecosystem activity in the absorption of greenhouse gases and, accordingly, the assessment of ecosystem services of this type is implemented using the RUDN's own environmental monitoring network, which has been operating since 2017. Preliminary assessments allowed us to draw conclusions about the degree of transformation of ecosystem components and their contribution to the absorption of greenhouse gases. The project has both practical and educational significance and is considered as part of the package of strategic topics for the development of the university